The Multiplier Concept and Monetary Restraint - Vernon, Jack (Quarterly Journal of Economics, 1974)
I. The problem. 330. — II. The rigid full employment constraint, 331. — III. A more flexible full employment constraint, 335. — IV. The positive sloping IS curve, 337. — V. Conclusions, 338.